Consumer Self-Confidence in Green Foods: An Investigation of the Role of Ecolabels Using the Theory of Planned Behavior and Market Segmentation. Issue 5 (20th October 2022) - D'Souza, Clare; Taghian, Mehdi; Apaolaza, Vanessa; Hartmann, Patrick; Brouwer, Anne; Chowdhury, Belal
Abstract: The research proposes a model based on the theory of planned behavior to examine the relationships on self-confidence with green foods, green consumer attitude, perceived behavioral control, social norms, label knowledge, and eco-labeling. Attitudes, social norms, and PBC were found to be significant Ecolabels mediate the relationship between attitudes and consumer self-confidence, while attitudes were found to mediate between label knowledge and intention to use ecolabels. The study contributes to a wider explanation of the impact of these contextual variables for eco-labels and provides support for both theory and practice that facilitate insights for business practitioners, policymakers, and consumer behavior theorists.